1990
DOI: 10.1017/s0956536100000067
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Activities in Classic Households: Two Case Studies from Coba and Teotihuacan

Abstract: Mesoamerican household sites were often deserted gradually, leaving very little de facto refuse for analysis. Starting with archaeological and paleobiological distribution patterns, this study adds a new dimension to the spatial study of two Classic households by plotting chemical concentrations in probable activity areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
16

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 1 publication
0
54
0
16
Order By: Relevance
“…Floor and soil chemistry studies have revolutionized household archaeology by providing supplementary lines of evidence to architecture and artifact distributions for discerning past activities in domestic spaces (Aguirre 2000; Aguirre and Barba 1990Barba , 2007Barba and Lazos 2000;Barba et al 1987Barba et al , 2007Manzanilla and Barba 1990;Mejía Pérez Campos and Barba 1991;Ortiz and Barba 1993;Tovalín and Barba 1999). Not only are these methods valuable in contexts of complex habitations with long occupation sequences and meticulously swept living surfaces, as is usually the case at urban centers with lime-plaster floors, but also for simpler house types, shorter occupations, and contexts with in situ artifacts on earth or sand floors.…”
Section: Montementioning
confidence: 99%
“…Floor and soil chemistry studies have revolutionized household archaeology by providing supplementary lines of evidence to architecture and artifact distributions for discerning past activities in domestic spaces (Aguirre 2000; Aguirre and Barba 1990Barba , 2007Barba and Lazos 2000;Barba et al 1987Barba et al , 2007Manzanilla and Barba 1990;Mejía Pérez Campos and Barba 1991;Ortiz and Barba 1993;Tovalín and Barba 1999). Not only are these methods valuable in contexts of complex habitations with long occupation sequences and meticulously swept living surfaces, as is usually the case at urban centers with lime-plaster floors, but also for simpler house types, shorter occupations, and contexts with in situ artifacts on earth or sand floors.…”
Section: Montementioning
confidence: 99%
“…For the study of past behavior in situations where artifactual data is poor, archaeologists have developed innovative methods. One of them is the analysis of microscopic remains, such as micro debitage of lithics and small botanical samples that are affected by abandonment processes in lesser degrees than ordinary artifacts (Fladmark, 1982;McGovern et al, 1983;Rosen, 1986Rosen, , 1989Manzanilla, 1987;Manzanilla and Barba, 1990;Metcalfe and Heath, 1990;Simms and Heath, 1990;Middleton, 1998). Nevertheless, in the Maya area where many buildings have well swept, smooth stucco floors and the preservation of organic materials is poor, the recovery of microscopic remains may not always be easy.…”
Section: Background Archaeological Study Of Maya Householdsmentioning
confidence: 99%
“…Modern-day activities associated with phosphate include gardening, waste handling, the storage and preparation of food, and sweeping that pushes organic material to the patio peripheries (Barba and Ortiz, 1992). Investigations carried out by Manzanilla and Barba (1990) establish some general chemical patterns of various ancient activities, such as rest or sleeping areas, areas of food preparation and consumption, and areas of heavy foot traffic (see also Barba et al, 1995;de Pierrebourg, 1999). We have used soil phosphate analysis at the Classic Maya site of Piedras Negras, Guatemala as a prospection tool to identify the locations of middens Wells et al, 2000).…”
Section: Soil Chemical Analysis In Archaeologymentioning
confidence: 99%
“…Extensive studies by Barba, Manzanilla and colleagues demonstrated that it was possible to identify different activity areas through changes in chemical concentrations with: rest/sleeping areas and thoroughfares being depleted in chemical compounds; food preparation areas having low phosphate values; and food consumption and animal penning areas having high phosphate values. They then used these results to interpret a number of archaeological sites in Mexico (Barba and Bello 1978;Barba and Denis 1981;Mejia and Barba 1988;Manzanilla and Barba 1990). Similarly, Middleton and Price (1996) analysed a range of floors from ethnographic and archaeological sites in Mexico.…”
Section: Geochemistrymentioning
confidence: 99%